Functionalized peptide hydrogels: enabling dynamic stage-adaptive modulation for wound healing - Ma, Xi-Kun; Peng, Qi; Miao, Gui-Hua; Zhang, Xiu-Zhen (Frontiers in Cell and Developmental Biology, 2025)
Functionalized peptide hydrogels represent an emerging class of intelligent wound dressings that dynamically coordinate the multifaceted process of wound healing through stage-specific bioactivities. By leveraging programmable molecular designs, these hydrogels actively engage with key healing phases—hemostasis, antibiosis, inflammation resolution, angiogenesis, and tissue remodeling—enabling spatiotemporal control over cellular behaviors and molecular cues. For instance, antimicrobial peptides (e.g., EPL, LL37, TCP-25) not only eradicate pathogens but also modulate macrophage polarization to mitigate excessive inflammation. Angiogenic factors (e.g., VEGF, SDF-1) are sustainably released to promote vascularization, while MMP-responsive components facilitate ECM remodeling by balancing collagen deposition and degradation. Additionally, integrin-binding motifs (e.g., RGD) enhance cell adhesion and migration, further accelerating re-epithelialization. With inherent self-healing, injectability, and microenvironmental responsiveness (e.g., to pH, enzymes, or ROS), these hydrogels adapt to dynamic wound conditions, offering synergistic therapeutic outcomes. Future directions include designing multi-stimuli-responsive systems, personalized peptide sequences, and advanced delivery platforms (e.g., 3D-printed scaffolds, cell/exosome-loaded hydrogels) to advance clinical translation in precision wound management and regenerative medicine.